An intense 60-day weight-loss course leads to an 18 kg body weight reduction and metabolic reprogramming of soldiers with obesity - Albores-Méndez, Exsal M.; Carrasco-Vargas, Humberto; Alaniz Monreal, Samary; Mayen Quinto, Rodolfo David; López García, Ernesto Diderot; Gutierrez Salmean, Gabriela; Medina-Quero, Karen; Vargas-Hernández, Marco A.; Ferreira Batista, Cesar Vicente; López-Hernández, Yamilé; Winkler, Robert (PeerJ, 2024)
Soldiers of the Mexican Army with obesity were subjected to an intense 60-day weight-loss course consisting of a controlled diet, daily physical training, and psychological sessions. The nutritional treatment followed the European Society of Cardiology (ESC) recommendations, incorporating elements of the traditional milpa diet in the nutritional intervention. The total energy intake was reduced by 200 kcal every 20 days, starting with 1,800 kcal and ending with 1,400 kcal daily. On average, the participants reduced their body weight by 18 kg. We employed an innovative approach to monitor the progress of the twelve soldiers who completed the entire program. We compared the untargeted metabolomics profiles of their urine samples, taken before and after the course. The data obtained through liquid chromatography and high-resolution mass spectrometry (LC-MS) provided insightful results. Classification models perfectly separated the profiles pre and post-course, indicating a significant reprogramming of the participants’ metabolism. The changes were observed in the C1-, vitamin, amino acid, and energy metabolism pathways, primarily affecting the liver, biliary system, and mitochondria. This study not only demonstrates the potential of rapid weight loss and metabolic pathway modification but also introduces a non-invasive method for monitoring the metabolic state of individuals through urine mass spectrometry data.
Keywords: Diet; Metabolomics; Defense; Weight loss; Public health; Obesity; Data mining; Mass spectrometry; Nutrition; Training